Intramyocellular Lipid Content in Human Skeletal Muscle - Schrauwen‐Hinderling, Vera B.; Hesselink, Matthijs K.C.; Schrauwen, Patrick; Kooi, Marianne Eline (Obesity (Silver Spring, Md.), 2006)
Fat can be stored not only in adipose tissue but also in other tissues such as skeletal muscle. Fat droplets accumulated in skeletal muscle [intramyocellular lipids (IMCLs)] can be quantified by different methods, all with advantages and drawbacks. Here, we briefly review IMCL quantification methods that use biopsy specimens (biochemical quantification, electron microscopy, and histochemistry) and non‐invasive alternatives (magnetic resonance spectroscopy, magnetic resonance imaging, and computed tomography).